Fisheries and governance: A case study of Upper Wardha reservoir, Maharashtra - Gautam, Pooja; Ananthan, P S; Jha, Bankim C; Ramasubramanian, V (Journal of the Inland Fisheries Society of India, 2021)
The present status of ecology, fisheries and fisheries governance of the Upper Wardha reservoir have been studied using published literature, primary fieldwork, and collated species-wise catch data from fishermen co-operative society and the Department of Fisheries. Shannon-Wiener index value of 2.52 for the year 2016-17 indicated a moderate level of fish species diversification, even though it was dominated by IMC (87.5%). With 15 commercially harvested fishes, species richness during May-June and species evenness (J=0.93) during post-monsoon indicated evenly distributed and rich fauna. The trophic metrics revealed the dominance of herbivores, detritivores, and omnivores (93.9%) in reservoir food web with less than the optimal presence of mid-level carnivores (3.7%) and the top-level predators. However, the total annual fish catch from the reservoir has increased from 278 tonnes (1997-98) to 672 tonnes (2017-18) sgowing 140% enhnacement in 20 years with an impressive CAGR of 6.4%. It also translated into a significant increase in fish productivity from just 12 kg ha-1 year-1 to 114 kg ha-1year-1 during the same time period. The growth had been quite emphatic during the last 5 years after the Nal Damyanti Sagar Matsaya Utpadan & Fishermen Co-operative Society obtained the lease of the reservoir. Good management practices and effective governance in the form of optimal and regular stocking of appropriate size fish seed, issue of fishing permits, fixing of a fair price for fishers, strict enforcement of conservation measures, efficient marketing arrangement and measures to encourage women in fishing related activities have begun to transform slowly both fisheries and fishers livelihoods in Upper Wardha reservoir region.Key words Reservoir; Ecology; fish; production; fisheries governance; India